2019
DOI: 10.1038/s41598-019-40460-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of physical activity and cognitive function and their potential correlation in convalescent patients of cerebrovascular disease

Abstract: Physical activity (PA) is known to influence cognitive function. However, the impact of PA on patients with cerebrovascular disease (CVD) has not yet been elucidated. PA and cognitive function have not been measured simultaneously over time, which makes it difficult to evaluate their relationship. The purpose of this study was to investigate the change in the amount of PA recorded by ActiGraph GT3X-BT and six test scores of cognitive function, and the relationship between them in 15 patients with CVD (six wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…A number of anatomical and functional imaging studies have shown that cerebellum function is affected in several cognitive and behavioral developmental disorders, such as attention deficit hyperactivity disorder, autism, and schizophrenia [ 7 ]. Importantly, this neurophysiological evidence corroborates the association between motor and cognitive development in children [ 10 ].…”
Section: Introductionsupporting
confidence: 80%
“…A number of anatomical and functional imaging studies have shown that cerebellum function is affected in several cognitive and behavioral developmental disorders, such as attention deficit hyperactivity disorder, autism, and schizophrenia [ 7 ]. Importantly, this neurophysiological evidence corroborates the association between motor and cognitive development in children [ 10 ].…”
Section: Introductionsupporting
confidence: 80%
“…Figure 2 illustrates that six studies showed positive associations [ 38 , 41 , 43 , 47 , 50 , 51 ] (i.e., more sitting resulting in better cognitive function), with most of these studies ( n = 4) using self-reported measures of total sedentary behaviour time [ 38 , 43 , 47 , 51 ]. Figure 2 also shows that 20 studies found negative associations [ 35 37 , 39 , 40 , 43 , 47 , 48 , 52 63 ] (i.e., more sitting resulting in worse cognitive function), with most of these studies ( n = 16) using a device to measure total sedentary behaviour time [ 35 37 , 40 , 47 , 53 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…Overall, two of the four included longitudinal studies observed positive, significant associations between LPA engagement (at one or more time points) and global cognitive status (Kojima & Nagano, 2019;Stubbs et al, 2017) and attention/processing speed (Kojima & Nagano, 2019) at follow up. Similar to the cross-sectional studies, no trends existed between sample size, measured activity levels and cognitive outcomes.…”
Section: Longitudinal Studiesmentioning
confidence: 97%
“…Similar to the cross-sectional studies, no trends existed between sample size, measured activity levels and cognitive outcomes. Two studies collected PA data at multiple time points, with collection periods ranging from a monthly basis for four months (Kojima & Nagano, 2019) to a five year follow-up period (Halloway et al, 2017). Given the extremely small number of included longitudinal studies, each with their own methodological limitations and differences in study design, it is difficult to draw any meaningful conclusions or identify trends.…”
Section: Longitudinal Studiesmentioning
confidence: 99%
See 1 more Smart Citation